The Role of Patent Foramen Ovale Closure in the Secondary Prevention of Cryptogenic Stroke: a Meta-Analysis Report - Pereira,Sónia P. Pinto (2020)
Abstract Background: Patent foramen ovale (PFO) closure has been compared to medical therapy for secondary prevention of recurrent cryptogenic stroke. Objectives: To produce an updated meta-analysis including only data from the primary analyses of clinical trials and to evaluate the role of PFO closure in the secondary prevention of recurrent stroke. Methods: Search in Medline (PubMed) and in ISI Web of Knowledge. Parameters under analysis and meta-analyses were: stroke, transient ischemic attack (TIA) and atrial fibrillation (AF). Comprehensive Meta-analysis Software V.2.0 (Biostat) was used. Random-effects analyses were carried out. A level of significance of 5% was used. Results: In this study six, randomized trials enrolling 3,750 patients were included. Unlike other published meta-analyses on the same topic, in this case, only clinical trial data, and not follow-up data, were used. PFO closure, as compared with medical therapy alone, demonstrated superiority in reducing the rate of recurrent stroke (risk ratio with PFO closure vs. medical therapy, 0.37; 95% confidence interval [CI], 0.17 to 0.78; p = 0.01). PFO closure did not offer a significant benefit in prevention of TIA (risk ratio with PFO closure vs. medical therapy, 0.96; 95% CI, 0.64 to 1.44; p = 0.85). Among patients assigned to closure group, an increased risk of atrial fibrillation was seen (risk ratio with PFO closure vs. medical therapy, 4.64; 95% CI, 2.38 to 9.01; p < 0.01). Conclusions: In patients with cryptogenic stroke who had a patent foramen ovale, a protective effect of closure was seen concerning the risk of recurrent stroke, but not regarding the prevention of TIA.